2015
DOI: 10.1371/journal.pone.0124600
|View full text |Cite
|
Sign up to set email alerts
|

MLViS: A Web Tool for Machine Learning-Based Virtual Screening in Early-Phase of Drug Discovery and Development

Abstract: Virtual screening is an important step in early-phase of drug discovery process. Since there are thousands of compounds, this step should be both fast and effective in order to distinguish drug-like and nondrug-like molecules. Statistical machine learning methods are widely used in drug discovery studies for classification purpose. Here, we aim to develop a new tool, which can classify molecules as drug-like and nondrug-like based on various machine learning methods, including discriminant, tree-based, kernel-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…The enzyme is active as a tetramer or dimer in a pH-dependent equilibrium. Every monomer consists of two domains: the N-terminal domain (amino acids , with a β-α-β dinucleotide binding site (amino acids [38][39][40][41][42][43][44]; and a second larger β+α domain, consisting of an antiparallel nine-stranded sheet. The dimer interface lies in a barrel arrangement in this second part of the G6PD molecule.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme is active as a tetramer or dimer in a pH-dependent equilibrium. Every monomer consists of two domains: the N-terminal domain (amino acids , with a β-α-β dinucleotide binding site (amino acids [38][39][40][41][42][43][44]; and a second larger β+α domain, consisting of an antiparallel nine-stranded sheet. The dimer interface lies in a barrel arrangement in this second part of the G6PD molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Naïve Bayes (NB) and k-nearest neighbor (KNN) algorithms have also been used to distinguish active molecules from inactive ones. SVM and naïve Bayesian classifications have been successfully employed to categorize lymphocyte-specific protein tyrosine kinase, cytochrome P450, and butyrylcholinesterase inhibitors [166]. Further studies also confirmed the use of SVM-based algorithms to rank molecules based on their activity, whereas BNN and RF are also utilized for activity prediction [167][168][169][170].…”
Section: Ai-based Interventions In Advanced Therapeuticsmentioning
confidence: 81%
“…Moreover, SVM is capable of nonlinear classification and deal with high-dimensional data. Thus, it has been applied in many fields such as computational biology, text classification, image segmentation and cancer classification (Vapnik, 2000;Korkmaz, Zararsiz & Goksuluk, 2015).…”
Section: Svm:svm Is a Classification Methods Based On Statistical Learmentioning
confidence: 99%